Can I Choose a Throwable Object for You? Perceiving Affordances for Other Individuals - Ji, Huichao; Pan, Jing Samantha (Frontiers in Psychology, 2019)
Throwing is an important motor skill for human survival and societal development. It has been shown that throwers can select throwable balls for themselves and ball throwability is determined by its size and weight. In this study, we investigate whether throwers can perceive ball throwability for other throwers (experimental confederates) and whether the perceived throwability for others also follows a size-weight relation. Like other types of affordances, throwability entails a scaling between the thrower and the throwing object. This requires knowledge about the thrower and the object. In this study, knowledge about the objects was gained by hefting balls of various sizes and weights; knowledge about the throwers was gained by interacting with throwers in person (Experiment 1) and by viewing videos of confederates throwing or photographs of the confederates standing (Experiment 2). In both experiments, participants were able to perceive throwability and choose throwable balls for confederates of different sexes and fitness levels. The throwable balls followed a size-weight relation, where bigger balls had to weigh more to be perceived as throwable as smaller balls. Furthermore, there was no difference between throwability perception based on in-person interaction, watching videos of confederates throwing and seeing pictures of the confederates standing. This suggests that the scaling of throwability is likely to be based on anthropometric information.